Resolução de problemas da pré-álgebra e álgebra para fundamental II do ensino básico com auxílio do modelo de barras - Queiroz, Jonas Marques dos Santos (2014)
The difficulties in learning and teaching of algebra can be detected in the school cycle 4 (8th and 9th grades) of the Elementary School II and throughout High School, such difficulties being present in all Brazilian schools. These difficulties arise from an institutional failure, in others words, in the transition from arithmetic to algebra, in the phase of pre-algebra which occurs at cycle 3 ( 6th and 7th grades) of the Elementary School II. When this transition is unsatisfactory this compromises the subsequent studies making the students feel not motivated in learning the content of algebra. Therefore, in this research project we planned and executed 6 (six) activities based on the methodology of Problem Solving based on the phases proposed by George Polya, along with the methodology of the Bar Model from Singapore Mathematics. The activities were carried out in seventh grade classrooms of Elementary School II of Instituto Educacional Estilo , Campinas, SP. The results of this dissertation suggests to teachers of Elementary School II didactical sequences of activities that they can use and enjoy in classroom practices, so that they can improve also their teaching and learning, contributing to the development of the students. With the objective of achieving a satisfactory transition from arithmetic to algebra, the activities were developed and based on problems solving, and then analyzed critically using the Problem Solving steps. After 6 (six) activities, we applied a diagnostic evaluation in order to analyze the results and to check if the activities contributed to a meaningful learning of algebra. The dissertation presents a theoretical study about teaching and learning algebra as well as a study on the methodologies of Problem Solving in classroom practice and Bar Model from Singapore Mathematics.